Preservice teachers' conceptions of Earth and environmental topics appropriate for K–5 learners. Issue 2 (3rd April 2018) - Ford, Danielle J.
ABSTRACT: With the release of the Next Generation Science Standards, the Earth and environmental sciences receive greater emphasis at all grade levels. These rigorous standards increase pressure on elementary teachers to possess strong science content and pedagogical content knowledge. They also require teachers to hold a set of beliefs compatible with the goals set out in the NGSS. Elementary teachers, who often have minimal preparation in Earth and environmental sciences and entrenched beliefs about teaching and science, may face unique challenges in adjusting to the new standards. We report on a survey of 175 preservice teachers' beliefs about Earth science topics they consider to be appropriate for children in grades K–5. Participants were surveyed on their thoughts about the appropriateness of 20 standards-based topics. Results indicate that preservice teachers are enthusiastic about topics connected to nature and the environment, but judge the appropriateness of topics based on their own interests, misunderstand the interests of children, and lack specific knowledge of the NGSS. These mixed results have implications for instruction in the Earth sciences and teacher preparation: It is important to consider not just the content preparation of preservice teachers but also the ways in which we engage their beliefs about that content.